Factors Influencing Adoption Of Double-Rowplanting System Ofhybrid Corn On Dry Land In Pringgabaya, East Lombok, West Nusa Tenggara Province - ., Sudirman; Tanaya, IGL Parta; Mahsunin, Tajidan (Archives of Business Research, 2018)
This research aimed to (1) know achievement level ofdouble-row planting system adoption of hybrid corn on dry land in Pringgabaya of East Lombok regency, (2) know the influence of internal and external factors both simultaneously and partially onthe adoption of double-row planting system of hybrid corn on dry land in Pringgabaya of East Lombok Regency.Unit of analysis in this study is farmers who implement the Specific Effort Program (UPSUS) of Hybrid corn Development in Pringgabaya of East Lombok Regency in 2017s. There was three villages determined by "purposive samplingmethode";North Pringgabaya, Labuhan Lombok, and Gunung Malang. Data obtained were analyzed by using descriptive methods and multiple linear regressions, with the following results: (1) The adoption of double-row planting system of hybrid corn is still in low level achievement (Adoption of <50%); there are only 26% of respondents are adopting the double-row planting system of hybrid corn. (2) Simultaneous test shows that the ten independent variables significantly influence the achievement level of the system adoption (p-value; 0,000 <α; 0,05). (3) In the partial test, it was found that there are 6 (six) independent variables that significantly influence (p-value <0,05) the achievement of the innovation adoption; (1) education level (X2), (2) attendance frequency in counseling (X6), (3) level of risk-taking (X7), (4) ease/ trialability (X8), (5) compatibility (X9), and (6) communication (X10), while the other 4 independent variables do not give significant effect on the achievement level of the innovation adoption (p-value> 0,05); (1) age (X1), (2) number of family worker (X3), (3) experience of planting corn (X4) and (4) cultivated area (X5).